Guidelines for the Diagnosis and Treatment of Psoriasis in China: 2019 Concise Edition# - Committee of Psoriasis, Dermatology Branch, Chinese Medical Association (Wolters Kluwer Health, 2020)
Abstract. Psoriasis is an immune-mediated chronic, recurrent, systemic inflammatory disease induced by the combination of hereditary and environmental factors. The etiology of psoriasis involves hereditary, immune, environmental, and other factors, and its pathogenesis is considered to involve excessive proliferation of keratinocytes or inflammatory activation of synovial cells and chondrocytes within joints; these processes are caused by an immune response that is mainly mediated by T lymphocytes and various other immune cells. Psoriasis is an incurable disease, and the goal of treatment is to control the progression of disease and maintain long-term efficacy. Treatment protocols should be based on the patients' conditions. Patients with mild psoriasis can be mainly treated with topical agents, and those with moderate to severe psoriasis can be treated with systemic medications. Targeted biological agents can be appropriately chosen for cases of psoriasis that are resistant to traditional systemic treatment. New drugs and treatments for psoriasis continue to evolve and emerge, and our updated guidelines are designed to deliver new achievements from China and to physicians worldwide and to keep pace with global progress on psoriasis research. Compared with the previous two editions, part of contents have been modified and revised in the present guidelines; this will further facilitate standardization and increase the efficiency of the diagnosis and treatment of psoriasis in China, and improve patients' quality of life.